Role of endovascular embolisation for curative treatment of intracranial non-Galenic pial arteriovenous fistula. Issue 2 (9th December 2020) - Jin, Hengwei; Meng, Xiangyu; Quan, Jiale; Lu, Yi; Li, Youxiang
Abstract : Background and purpose: The safety and effectiveness of endovascular treatment for non-Galenic pial arteriovenous fistula (NGPAVF) is inadequately known. The aim of this study is to explore the role of endovascular embolisation for curative treatment of NGPAVF. Materials and methods: Patients with NGPAVF underwent endovascular treatment from January 2011 to November 2019 in our institution were retrospectively reviewed. Demographics, clinical information, treatment details and clinical outcomes were collected. Factors associated with clinical outcomes were statistically analysed. Results: Twenty patients were included, with a total of 22 (2 patients have 2 fistulas) lesions. A total of 25 procedures were performed and 5 patients underwent 2 procedures. Follow-up ranged from 3 to 84 months (mean=34.5 months). Thirteen (59.1%) lesions in 12 (60.0%) patients acquired immediate occlusion after initial treatment (immediately occluded group) and follow-up confirmed the complete obliteration. A total of 17 (77.3%) lesions in 15 (75.0%) patients were cured at last follow-up. The maximal diameter of feeding arteries (p=0.04) and the maximal diameter of the varix (p=0.01) in immediately occluded group was smaller than non-immediately occluded group. The number of feeding artery (p=0.004) and the maximal diameter of the varix (p<0.001) were much smaller in curative group than non-curative group. Seven patients suffered procedure-related complications. No patients had an increased Modified Rankin Scale (mRS) and all patients had favourable clinical outcome (mRS ≥2) at last follow-up. Conclusions: Endovascular therapy plays an important role in curative treatment of NGPAVF. Patients with less feeding arteries and small varix may be easier to be cured by endovascular embolisation.